Journalists as Spin Doctors: Perspectives on Journalist Hangout - Stephen Victor Gana; Daniel O. Ekhareafo (Budapest International Research and Critics University, 2024)
This study examined the role of journalist hangouts as spin doctors, focusing on how this gathering influence the framing of news stories in Nigeria, promote specific narratives, and affect public perception of media credibility. The specific objectives are to; assess the extent of influence these hangouts have on news framing, investigate their role in reinforcing narratives and agendas, and evaluate the implications of spin doctoring on public trust. Framing theory provides the theoretical framework, emphasising how media professionals shape narratives through their interactions. The study employed a mixed-methods approach, including quantitative surveys and qualitative thematic analysis, to gather and interpret data from journalists. Findings reveal that journalist hangouts significantly impact news framing and agenda-setting, with a general agreement on their role in reinforcing media narratives. However, the direct effect of spin doctoring on public trust is less clear, although there is consensus that the public is aware of manipulation. The study concludes that while journalist hangouts is influential, ethical training, transparency in reporting, and the inclusion of diverse perspectives are essential to mitigate negative impacts and enhance media credibility. Recommendations include strengthening ethical training for journalists, promoting transparency in news reporting, and encouraging diverse viewpoints to ensure balanced media coverage.